2013
DOI: 10.1159/000355947
|View full text |Cite
|
Sign up to set email alerts
|

The Human IgE Repertoire

Abstract: IgE is a key mediator in allergic diseases. However, in strong contrast to other antibody isotypes, many details of the composition of the human IgE repertoire are poorly defined. The low levels of human IgE in the circulation and the rarity of IgE-producing B cells are important reasons for this lack of knowledge. In this review, we summarize the current knowledge on these repertoires both in terms of their complexity and activity, i.e. knowledge which despite the difficulties encountered when studying the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 147 publications
5
30
0
Order By: Relevance
“…This previous finding is in accordance with several other recent publications (reviewed in Ref. 10) that also found that human IgE repertoires are oligoclonal. However, this finding does not apply to all atopic disease entities.…”
Section: Discussionsupporting
confidence: 93%
“…This previous finding is in accordance with several other recent publications (reviewed in Ref. 10) that also found that human IgE repertoires are oligoclonal. However, this finding does not apply to all atopic disease entities.…”
Section: Discussionsupporting
confidence: 93%
“…HTS libraries were additionally prepared from cDNA template so that the isotype encoded by each sequence could be identified. The IgE repertoires of these samples revealed relatively few (<150/donor) distinct IgE-encoding rearrangements, compared to rearrangements encoding other isotypes, before initiation of SIT despite the fact that the number of reads per unique sequence was substantially larger for the IgE population in comparison to other isotypes (Supplementary Tables EII–EIV in the Online Repository), in agreement with findings obtained by conventional sequencing approaches (15). …”
Section: Resultssupporting
confidence: 86%
“…Characterization of IgE repertoires in general has been addressed in several studies (reviewed by Gadermaier et al (15)). These pioneering investigations have provided useful insights into the characteristics of IgE repertoires, such as their oligoclonal nature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, considering the heterogeneity in the immunological response and the polyclonality of the IgE repertoire (Gadermaier et al, 2014), we decided to perform a study in a large set of patients (n = 79) to attempt to identify the domains of the protein most often involved in IgE recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The major event is the cross-linking of IgE on mast cells and basophils, leading to the release of the inflammatory mediators responsible for the immediate reaction, but other immunological mechanisms involving IgE antibodies have also been described (Acharya et al, 2010;van der Heijden et al, 1993;Ying et al, 2001). However, despite the pivotal role established for IgE in allergic reactions, little is known about the interaction between allergens and antibodies, mainly due to the low concentration of this class of immunoglobulin in the sera of patients and to the fact that IgE-producing B cells have been poorly characterized [reviewed by (Gadermaier et al, 2014)]. Most of the data related to this aspect are derived from in vitro assays using mouse monoclonal antibodies and/or recombinant chimeric human IgE derived from mouse antibodies (Tai et al, 2013;Tiwari et al, 2012).…”
Section: Introductionmentioning
confidence: 99%